Climate-Resilient Sustainability Strategy as a Catalyst for Growth and Innovation of Banking Corporates in Asia and Africa - Duraisamy, Buvaneswari (Digital Repository of Theses - SSBM Geneva, 2025)
Climate change is a potential threat in this modern era as it affects several sectors. The business of the modern era tries to be focused on implementing climate change strategies for combating the crisis of the climate. In this regard, the banking sector has initiated sustainable practices such as green practices, and digitalisation that help this sector to reduce its carbon footprint. Sustainability strategies of the banks and other financial institutions have been discussed in the background of this research, apart from that the problems that are created for implementing these practices and it has been elaborated in the problem statement section. This research has aimed to demonstrate the relevance of the incorporation of strategic approaches relating to sustainability and climate resilience on the growth and innovation performance of banking organisations operating in Africa and Asia. The usage of an interpretivism research philosophy is expected to demonstrate previously published information. The research used primary qualitative data collection through interviewing twenty-three participants from the Asian and African banking sector, and thematic analysis for data analysis. It should also be mentioned that reliability test has been included within the study which will ensure the validity of the research. Some significant ethics has been maintained throughout the research process as it helps the research to be more meaningful and reliable. Climate resilient strategies are significant aspect for financial corporate as they help to mitigate the climate vulnerability and handle the haphazard situation. The climate resilient strategies that address the climate vulnerability have been discussed in this topic. Green financing which is an innovative strategy for the finance companies to develop their sustainable planning has been elaborated in this topic. Climate resilient sustainable strategies have an effective role in the profitability of the finance company that has been discussed in this topic. Climate resilience strategies implemented by financial institutions and banks in the banking sector have impactful incorporation of innovation and strategies for combating climate change that affect business performance of companies. Furthermore, climate resilience strategies influencing the development of sustainable solutions and digital innovations for empowering climate concerns acknowledgement among companies have also been discussed. Climate resilience is capable of being implemented as corporate strategy, and it faces certain threats and challenges, both financial and non-financial in nature. Moreover, climate resilience and its contributions to innovative financial solutions have also been discussed. Keywords: Climate change, banking sector, financial sector, climate resilience, innovation, sustainability, ESG factors